Bleda S. Düring and Claudia Glatz (eds), Kinetic Landscapes, the Cide Archaeological Project: Surveying the Turkish Western Black Sea Coast - Crow, James (Journal of Greek Archaeology, 2021)
Archaeological knowledge of the Black Sea coast of Turkey is limited for all periods of history and prehistory. Lacking the instant appeal of the Classical to Roman monuments of the south and west coasts, or the universal prehistoric interest of sites like Çatal Höyük or Göbekli Tepe, the deeply forested and often inaccessible mountainous Black Sea coast remains largely neglected. The name Cide derives from the ancient Kydros (mod. Gideros), a modest Classical town set between the major coastal cities of Amastris (Amasra) in the west and Sinope (Sinop) - once capital of Mithradates’ empire - to the east.